2002
DOI: 10.1073/pnas.262589799
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of DNA alkylation damage by two human dioxygenases

Abstract: The Escherichia coli AlkB protein protects against the cytotoxicity of methylating agents by repair of the DNA lesions 1-methyladenine and 3-methylcytosine, which are generated in singlestranded stretches of DNA. AlkB is an ␣-ketoglutarate-and Fe(II)-dependent dioxygenase that oxidizes the relevant methyl groups and releases them as formaldehyde. Here, we identify two human AlkB homologs, ABH2 and ABH3, by sequence and fold similarity, functional assays, and complementation of the E. coli alkB mutant phenotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
385
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 378 publications
(394 citation statements)
references
References 29 publications
8
385
0
1
Order By: Relevance
“…m 1 A has recently been discovered as another mRNA modification, in addition to m 6 A, pseudouridine, and m 5 C. The presence of m 1 A at the 5′ UTR region in mRNA has been suggested to promote translation (Dominissini et al, 2016;Li et al, 2016). ALKBH3, a DNA repair enzyme that demethylates N 1 -methyldeoxyadenosine in single-stranded DNA (Aas et al, 2003;Duncan et al, 2002) has been suggested as a potential demethylase of m 1 A in mRNA , the functional relevance of which still requires further investigations. ALKBH3 is also capable of repairing tRNA alkylation damages (Aas et al, 2003), again the biological relevance of which was not clear.…”
Section: Trna M 1 a Demethylation By Alkbh1mentioning
confidence: 99%
“…m 1 A has recently been discovered as another mRNA modification, in addition to m 6 A, pseudouridine, and m 5 C. The presence of m 1 A at the 5′ UTR region in mRNA has been suggested to promote translation (Dominissini et al, 2016;Li et al, 2016). ALKBH3, a DNA repair enzyme that demethylates N 1 -methyldeoxyadenosine in single-stranded DNA (Aas et al, 2003;Duncan et al, 2002) has been suggested as a potential demethylase of m 1 A in mRNA , the functional relevance of which still requires further investigations. ALKBH3 is also capable of repairing tRNA alkylation damages (Aas et al, 2003), again the biological relevance of which was not clear.…”
Section: Trna M 1 a Demethylation By Alkbh1mentioning
confidence: 99%
“…AlkB repairs various modifications as shown by the survival of alkylated bacteriophage in an E. coli alkB mutant [32,37,46,60,61]. Mainly, AlkB is known for the repair of 1-meA and 3-meC.…”
Section: Substratesmentioning
confidence: 99%
“…3, and studies have confirmed that 1-ethyladenine is repaired by AlkB to form adenine [37]. The C-1 C-H group rather than the C-2 C-H group of the ethyl adduct is oxidized, forming acetaldehyde as the released product along with the repaired base [37].S N 2 alkylating epoxides can cause hydroxyalkylated DNA lesions. For instance, ethylene oxide and propylene oxide can form 1-hydroxyalkyladenine and 3-hydroxyalkylcytosine.…”
mentioning
confidence: 99%
“…AlkB, hABH1, hABH2 and hABH3 have a similar specificity for 1-meA and 3-meC, but they exibit different selectivity for ss or double-stranded (ds) DNA/RNA substrates. hABH2 was found to be strikingly more active on dsDNA than on ssDNA (Duncan et al, 2002;Aas et al, 2003). By contrast, hABH1 and hABH3 strongly prefer ssDNA/RNA as substrates (Duncan et al, 2002;Aas et al, 2003;Westbye et al, 2008), whereas AlkB has a slightly higher activity toward ss than ds nucleic acids (Falnes et al, 2002).…”
Section: Alkb-family Dna/rna Demethylase and Substrate Selection Mechmentioning
confidence: 93%
“…Eight AlkB homologs are predicted to exist in human (Kurowski et al, 2003). Removal of the methyl group from 1-methyladenine (1-meA) and 3-methylcytosine (3-meC) through oxidation by AlkB family protein has been experimentally demonstrated for E. coli AlkB (Falnes et al, 2002) and its human homologs hABH1 (Westbye et al, 2008;Müller et al, 2010), hABH2 (Duncan et al, 2002;Aas et al, 2003) and hABH3 (Duncan et al, 2002). In addition to DNA, RNA can also act as substrates of some AlkB members like AlkB, hABH1 and hABH3 (Aas et al, 2003;Westbye et al, 2008).…”
Section: Alkb-family Dna/rna Demethylase and Substrate Selection Mechmentioning
confidence: 99%